Novel anti-corrosion coatings on steel. - Andrew Richard Bennett (2009)
The primary objective of the work detailed in this thesis was to further explore the inhibitory performance of polyaniline for the prevention of corrosion-driven cathodic disbondment on steels and zinc-alloy coated steels. Polyaniline was investigated under atmospheric conditions so as to make possible further elucidation of the mechanisms by which it would provide this inhibition. Accordingly it is suggested that the positive performance of polyaniline indicated within this report, in addition to further mechanistic understanding, paves the way for industrial use of polyaniline as an inhibitor. To provide further mechanistic support to the inhibitory performance of polyaniline, polyaniline micro-films were applied to the metal substrate surfaces, allowing the visualisation of electrochemical and acid-base state changes resulting from substrate contact and corrosion. Due to industrial concerns over the current cost associated with polyaniline inhibitor pigments, the inhibitory properties of novel organic acid etch primers were explored on both iron and zinc substrates. The findings of this study led to the proposition that the presence of polyaniline may not be required within the model organic coating system in order to provide a similar level of inhibition. Alongside the investigations of inhibitory organic coating systems, attention was directed towards novel Mg-Al-Zn metallic coatings. These are shown to provide inhibition of cathodic disbondment of organic coatings where no form of in-coating inhibition is present. These alloy-coated steels were found to suffer from a novel form of corrosion and full mechanistic proposition is provided, as well as important initiation factors. Finally, the photovoltaic possibilities of polyaniline were explored in order to find novel, high value coating systems for the pre-painted steel industry. Accordingly the photovoltaic properties of polyaniline are compared to established photovoltaic polymers.